2020
DOI: 10.3389/fped.2020.00578
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Do Better? Learning From 617 Pediatric Patients With Airway Foreign Bodies Over a 2-Year Period in an Asian Population

Abstract: Background: Foreign body (FB) in the pediatric airway is a prevailing and crucial emergency with presenting symptoms often overlapping with other common pediatric conditions. There are limited number of large cohort studies in an Asian population which demonstrate the diversity of symptoms, investigations which will aid in obtaining the diagnosis, and management. Using this large cohort, we aim to evaluate the type and location, clinical presentations and outcomes of medical management related to pediatric air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…Chest CT scan was taken in 2 patients; it was avoided to reduce exposure to ionizing radiation. In this study, right bronchial tree was the most common site of impaction, like reported by the previous studies (Chisholm and Johnson, 2018;Gao et al, 2020). It is mostly due to the position and wider diameter of the right bronchi.…”
Section: Resultssupporting
confidence: 82%
“…Chest CT scan was taken in 2 patients; it was avoided to reduce exposure to ionizing radiation. In this study, right bronchial tree was the most common site of impaction, like reported by the previous studies (Chisholm and Johnson, 2018;Gao et al, 2020). It is mostly due to the position and wider diameter of the right bronchi.…”
Section: Resultssupporting
confidence: 82%
“…In the present study, the most common location of FBs was the right main bronchus (38.33%). Because the right bronchus is straighter and has larger diameter than the left, entrapment of FBs is more likely in this bronchus ( 25 ), and our finding is consistent with the results of most retrospective studies previously conducted ( 6 , 9 , 17 , 18 , 26 , 27 ), but inconsistent with the findings of a few studies ( 8 , 11 ). Given the observation of multiple FBs in 64 cases (4.82%) in the present study, it is important to explore the complete bronchial tree systematically when searching for FBs.…”
Section: Discussionsupporting
confidence: 78%
“…The diverse types of FB depended on eating habits, parentral supervision, and cultural influences, especially in Asian families. 20,39 With the development of urban life, grandparents have taken on the responsibility of caring for children. Despite this, they are unaware of food choking hazards and feed the children to the same food that they eat.…”
Section: Types Of Aspirated Foreign Bodiesmentioning
confidence: 99%
“…This could be due to the mechanical and chemical irritation of organic FBs, which causes more granulation formation in the airways. 20 Therefore, some foods necessitate more skill. Nutritionists for example, should recommend peanuts to school-aged children who have developed mastication skills.…”
Section: Types Of Aspirated Foreign Bodiesmentioning
confidence: 99%
See 1 more Smart Citation